Study of fetomaternal outcome in first trimester bleeding per vaginum - Patel, Hemilkumar Hasmukhbhai; Shihora, Kartavya Yashodharchandra; Patel, Margi Rajendrakumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: First trimester vaginal bleeding is a frequent obstetric problem affecting 20–25% of pregnancies and is associated with anxiety and adverse pregnancy outcomes. It may range from benign causes to life-threatening conditions and can significantly influence fetal and maternal prognosis. Methods: This retrospective observational study was conducted at Sub district hospital Gandhidham Bhuj Kutch over 9 months and included 40 pregnant women presenting with vaginal bleeding in the first trimester. Data regarding age, parity, obstetric history, ultrasound findings, management and pregnancy outcomes were collected from hospital records and analyzed. Results: Most women were aged 21–30 years and 62.5% were primigravida. Ultrasound findings included normal scans, incomplete and missed abortions, anembryonic gestation, ectopic pregnancy and subchorionic hematoma. Conservative and medical management was used in threatened cases, while surgical intervention was required in non-viable pregnancies. Eighteen women had viable outcomes, with 13 delivering live babies. Conclusions: First trimester bleeding is a high-risk condition associated with increased miscarriage and adverse obstetric outcomes. Early diagnosis, close monitoring and proper counselling are essential to improve feto-maternal outcomes.